The Role of the State Government in Resolving Social Conflicts Between Ureng Country and Negeri Lima - Raihana Kelutur; Jumiati Tuharea; Aisa Abas (CV. Rayyan Dwi Bharata, 2022)
On the other hand, the diversity of the multicultural society as the wealth of the Indonesian nation is very prone to triggering conflict and division. The diversity of Indonesian society can at least be seen from its two unique characteristics. First, horizontally, marked by the fact that there are social units based on differences in ethnicity, religion, customs and regional differences. Second, vertically, marked by a sharp vertical difference between the upper and lower layers. Humans as social beings and as individuals always need interaction with others. In social interaction itself there is always conflict or cooperation between them. Thus, conflict can be said to be a natural part of human life. The purpose of this research is to find out. 1. To find out the solutions of state government in resolving social conflicts between Negeri Ureng and Negeri Negeri Lima. 2. To find out the inhibiting factors of state government in resolving social conflicts between Negeri Ureng and Negeri Negeri Lima. The type of research used in this study is descriptive qualitative, namely a systematic factual and accurate description of the factors in the field that are related to matters in the field. The data in this study were collected using observation and documentation methods. Data Analysis Techniques. The data obtained from the results of this study were compiled and analyzed qualitatively, then the data was described descriptively in order to obtain a clear and directed picture of how to answer the problem. The results of the research on the Role of Community Leaders in Resolving Social Conflict in Negeri Ureng and Negeri Lima are very important as, the conflict between these two countries has been going on for so long, so the role of these community leaders is very important because they become pawns to prevent conflict between the two countries, by him it is necessary to further increase the capacity and strengthen the position holders as people who are influential in occupying existing positions in this country so that when there is an issue from these two countries the role of community leaders is very helpful in resolving the conflict.